PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN KERIPIK SUHER - Yopyter Promanjoe (Jurnal Performa : Jurnal Manajemen dan Start-up Bisnis, 2021)
Customer Relationship Management is a long-term business strategy to establish relationships with customers. Through the right customer relationship marketing, customer satisfaction and loyalty can be formed. This study aims to examine the effect of customer relationship management on customer satisfaction and loyalty, as well as to examine the influence of customer relationship management and customer satisfaction on customer loyalty. Respondents are 85 consumers of Keripik Suher in Surabaya, which were taken by using purposive sampling method. The analysis used Partial Least Squares (PLS). The results of hypothesis testing indicate that customer relationship management has a positive effect on customer satisfaction and loyalty of Keripik Suher, and also customer satisfaction has a significant positive effect on customer loyalty of Keripik Suher. So it can be concluded that the higher customer relationship marketing and customer satisfaction will increase customer loyalty. Keywords: Customer Relationship Management, Customer Satisfaction, Customer Loyalty